Hábitos alimentarios y su relación con el estado nutricional en adultos del sector puertas al cielo-Vinces. Periodo académico octubre 2024-mayo 2025. - García Quiñonez, Thayli Kimberly (2025)
Eating habits are justified for health and well, especially for young adults, which is the main stage in physical and psychological development. The type of food affects your daily energy and nutritional status which affects the prevention of chronic diseases. Insufficient food can lead to nutritional deficiencies or contribute to obesity and obesity. In the context of globalization and processed foods, food patterns change in the context of short- and long-term health. It is important to explore how eating habits affect dietary status for young adults aged 20 to 30, which is an essential phase of eating patterns that will affect their future health. Objective: Determine the relationship between eating habits and nutritional status in adults from the Puertas al Cielo-Vinces Sector. Academic period October 2024 – May 2025. Methodology: This research was descriptive, cross-sectional, field, correlational, non-experimental. With a qualitative-quantitative approach to obtain a comprehensive vision of the phenomenon. Results: 34% of respondents consume fruits in a moderate amount (1-2 servings daily), while only 15% meet the daily recommendation, suggesting insufficient intake of these foods. In contrast, 35% consume ultra-processed foods between 1 and 2 times a week, and 14% between 3 and 5 times, which indicates a significant presence of these products in the diet. Regarding nutritional status, 31% of the participants have a healthy weight, while 13% are overweight and 4% obese, evidencing a prevalence of excess weight. Conclusion: The analysis of the eating habits and nutritional status of adults in the Puertas al Cielo-Vinces Sector presents a relatively stable eating routine, with breakfast and lunch being the most frequent meals.